Investigation of Energy-Efficient Solutions for a Single-Family House Based on the 4E Idea in Poland - Piotr Ciuman; Jan Kaczmarczyk; Dorota Winnicka-Jasłowska (Energies)
The paper analyses multi-variant energy simulations carried out in IDA ICE 4.8 software for a newly designed single-family building within the framework of the 4E Idea. This idea assumes the use of energy-saving, ecological, ergonomic, and economic solutions in construction and building operation. Energy simulations were conducted to evaluate the annual energy-saving potential of the developed architectural house concept, which incorporates ergonomic analyses and cost-effective construction solutions. Analyses were conducted to optimise the non-renewable primary energy index by selecting mechanical ventilation system (CAV or VAV) with heat recovery; the configuration of photovoltaic module installation in terms of their location and orientation; the exposure and type of solar thermal collectors (flat and vacuum); and the use of two types of heat pumps (air- and ground-source). The most favourable energy performance of the building was achieved with an HVAC system equipped with a VAV mechanical ventilation system with heat recovery, an on-grid photovoltaic installation, vacuum solar thermal collectors, and a ground-source heat pump with a horizontal heat exchanger. This configuration resulted in a primary energy index value of 2 kWh/m2/year. The results of the analyses carried out for the 4E building concept may serve as a reference point for future energy-efficient building designs aspiring to meet higher standards of sustainable development.